PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA - Fitranita, Vika; Kamaludin, Kamaludin; Midiastuty, Pratana Puspa (UNIB Press, 2017)
The purpose of this research is to analyze the influence of corporate governance mechanisms, namely proportion of independent commissioner, audit committee, and foreign ownership toward the earnings management.The populations of this research were the manufacturing companies listed in Indonesian stock exchange 2011-2013. Based on purposive sampling tecnique that sample was taken 70 manufacturing companies.The result of this research show that the proportion of independent commissioner has negative significant influence toward the earnings management, while audit committee and foreign ownership has no significant influence toward the earnings management. The results of this study have implications for investors in the context of decision making based on the company reported earnings. Companies that have a large proportion of independent commissioner is more qualified than the companies that have a small proportion of independent commissioner.